PENGGUNAAN MULTIMEDIA DALAM PEMBELAJARAN TEORI KINETIK GAS DI SMA/MA NEGERI DAN SWASTA KECAMATAN SAMBAS - Afriana, Jaka (Universitas Tanjungpura, 2013)
Using Multimedia in Learning Kinetic Gas Theory in SMA / MA Public and Private District of Sambas. This study aims to see changes in student learning outcomes after learning using multimedia by comparing the value of the learning outcomes of the pre-test and post-test. Quasi-experimental methods used in this study with one group pretest-posttest design. Research subjects choose three of four SMA/ MA Public and Private District of Sambas which has a program of Natural Sciences, SMA Negeri 1 Sambas (20 students), MAN Sambas (19 students), and SMA Santo Bonaventura (16 students). Based on the data analysis and discussion, the average percentage of learning outcomes pre-test on Gas Kinetic Theory of 53.68% of the 55 students. While the average percentage of learning outcomes post-test 69.04% of the 55 students. The increase in the average percentage of student learning outcomes in the material Kinetic Theory of Gases using multimedia for 15.37%. The results of calculations using the McNemar test, of the total ten questions occur to improving student learning outcomes Gas Kinetic Theory of matter between before and after learning using multimedia, which calculate the average X2 mean = 9.10 and X2table mean = 3.84 this means that the calculated X2hitung > X2table. Keywords : Multimedia, kinetic theory of gases.